Characterization of Bacillus thuringiensis native isolates from Colombian natural forest and agricultural fields - YARA, ERICA; CERÓN, JAIRO; URIBE, DANIEL (Revista Colombiana de Entomología, 1999)
Bacillus thuringiensis (Berliner) is the most worldwide used entomopathogenic microorganism for the biological control of pest insects. In the same way, it is known as a very cosmopolite microbe, with the capacity to grow in a variety of ecosystems such as tropical rain forests or desert areas. Instead of the wide ecological distribution of the specie, most of the studies related with the isolation of B. thuringiensis (Bt), have been using, soil samples from agricultural ecosystems, where it is found the pest insect we wish to control. In this study, we compare the presence of Bt in soil samples from the native forest of the National Natural Park Katios (PNN Katios) and different agricultural ecosystems (coffee, tobacco, grass, potato, and others). In order to accomplish these aims, we took seven soil samples from PNN Katios and 21 from the agricultural ecosystems which were analyzed by the methodology of Travers et al. (1987). Twenty-nine strains were obtained from 28 soil samples. Twentyones of these strains are from PNN Katios. Eighty-three percent of the strains from the native rain forest had atypical patterns in terms of the inclusion bodies and the electrophoretic profile of the proteins of such bodies. On the other hand, from the agricultural soil samples, it is important to remark the strain IBUN115A32 which presented crystals of three different shapes and the strain IBUN97B 1 which presented, in the PCR reaction, a DNA band of different size which may suggest the presence of a new cry gene. The results obtained in this study confirm the importance of the screening of new Bt strains in order to know the real diversity of Bt.